Laboratory validation of the hole-drilling technique on the most common load-bearing walls used in heritage constructions. (20th April 2018) - Lombillo, I.; Blanco, H.; Villegas, L.; Boffill, Y.
Highlights: Hole-drilling technique applied in laboratory to several masonry walls. Satisfactory results achieved in sandstone ashlars and rammed-earth walls. Poorer results obtained in the case of rubble-stone masonries. Optical fiber strain gauges were used to perform one test. The results were adequate. Digital image correlation and tracking were also used. The results were inadequate. Abstract: The article describes the application of hole-drilling in diverse constructive types, detailing the results achieved in calibration tests carried out on several laboratory-built walls. The theoretical stress levels were approximated very closely in the case of ashlar (0.96) and rammed earth (0.91), but less closely in the brick wall (0.61). The technique did not prove useful with rubble-stone walls, although the cause of the discordance was not related to the methodology employed. Additionally, a comparison was established among hole-drilling tests carried out with different deformation recording techniques.